DC-DC boost converter based MSHE-PWM cascaded multilevel inverter control for STATCOM systems - Law, Kah Haw; Dahidah, M. (IEEE, 2014)
This paper investigates the performance of Static Synchronous Compensator (STATCOM) with the new variation of multilevel selective harmonic elimination pulse width modulation (MSHE-PWM). The proposed MSHE-PWM optimizes both the dc-voltage levels and the switching angles, enabling more harmonics to be eliminated without affecting the structure of the inverter circuit. The method also provides constant switching angles and linear pattern of dc voltage levels over the modulation index range. This in turns eliminates the required tedious steps for manipulating the off-line calculated switching angles and therefore, easing the implementation of the MSHE-PWM for dynamic systems. The required variable dc voltage levels are obtained from simple dc-dc boost converter. Current and voltage closed loop controllers are implemented for both the STATCOM and the boost converter to meet the reactive power (VAR) demand for different loading conditions. The proposed approach is validated through both simulation and experimental results.